2019
DOI: 10.1002/lary.28059
|View full text |Cite
|
Sign up to set email alerts
|

Extranodal extension is a strong prognosticator in HPV‐positive oropharyngeal squamous cell carcinoma

Abstract: Objective To comprehensively examine the prognostic significance of extranodal extension (ENE) in human papillomavirus–positive oropharyngeal squamous cell carcinoma (HPV‐positive OPSCC). Methods Retrospective cohort of cases diagnosed with HPV‐positive OPSCC from 2010 to 2015 in the National Cancer Database. Inclusion of all OPSCC HPV‐positive cases with appropriate International Classification of Diseases‐0‐3 codes that received surgery with a neck dissection. Univariate and multivariable analyses were condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(79 citation statements)
references
References 27 publications
4
72
1
2
Order By: Relevance
“…For instance, Bauer et al in their 2019 study illustrated the importance of the extent of ENE in patients with OPSCC (5). Patients were classified into the categories ENE-negative, microscopic ENE, and macroscopic ENE, and patients with microscopic ENE showed significantly reduced survival compared to patients with negative ENE status (hazard ratio = HR = 1.52; 95% CI = 1.00-2.31; p = 0.048) (5). Patients with macroscopic ENE had the worst outcome (HR = 2.50; 95% CI = 1.39-4.51; p = 0.002) (5).…”
Section: Definition Of Extranodal Extensionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, Bauer et al in their 2019 study illustrated the importance of the extent of ENE in patients with OPSCC (5). Patients were classified into the categories ENE-negative, microscopic ENE, and macroscopic ENE, and patients with microscopic ENE showed significantly reduced survival compared to patients with negative ENE status (hazard ratio = HR = 1.52; 95% CI = 1.00-2.31; p = 0.048) (5). Patients with macroscopic ENE had the worst outcome (HR = 2.50; 95% CI = 1.39-4.51; p = 0.002) (5).…”
Section: Definition Of Extranodal Extensionmentioning
confidence: 99%
“…Patients were classified into the categories ENE-negative, microscopic ENE, and macroscopic ENE, and patients with microscopic ENE showed significantly reduced survival compared to patients with negative ENE status (hazard ratio = HR = 1.52; 95% CI = 1.00-2.31; p = 0.048) (5). Patients with macroscopic ENE had the worst outcome (HR = 2.50; 95% CI = 1.39-4.51; p = 0.002) (5). In addition to that, recent data even differentiate between the categories "no ENE, " "minimal ENE" (≤1 mm beyond the lymph node capsule"), and ">1 mm beyond the lymph node capsule" (6).…”
Section: Definition Of Extranodal Extensionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies found the presence of pENE not to be a prognostic factor while others showed that only grade 4 pENE, in the form of soft tissue metastasis, to impact survival. 7,9,10,[33][34][35] Although there was no systematic reporting of pENE grade that was meta-analyzable, Patel et al described the extent of pENE for matching rENE in HPV-positive HNSCC. This study defined macroscopic pENE as greater than 2 mm of extension beyond the capsule, and found that radiographic nodal size ≥3 cm had significant correlation with macroscopic pENE.…”
Section: Discussionmentioning
confidence: 99%
“…Head and neck squamous cell carcinoma (HNSCC) is an invasive cancer that originates in the oral cavity, larynx, and pharynx, in association with alcohol and tobacco use or exposure to human papillomavirus (1)(2)(3). While much of the morbidity of HNSCC is caused by local invasion into nerve and vascular tissues of the neck, mortality is driven primarily by metastasis to regional lymph nodes and distant organs (4)(5)(6)(7). A key event that facilitates this metastasis is tumor-associated lymph and blood vessel formation ( Figure 1A).…”
Section: Introductionmentioning
confidence: 99%